ALG3 as a prognostic biomarker and mediator of PD-1 blockade resistance in hepatocellular carcinoma - Tang, Pengju; Han, Zhenwei; Zhao, Yiming; Xu, Tianxin; Zhang, Yu; Zhu, Lirong; Song, Fei; Gao, Cheng; Gong, Jinbo; Cheng, Ji; Wang, Chenggui; Wang, Tianlun; et al. (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a leading cause of cancer-related death globally, characterized by high heterogeneity and drug resistance, which significantly impacts clinical outcomes. The tumor microenvironment (TME) plays a critical role in HCC initiation and progression, with immune cell infiltration and immune checkpoint expression closely linked to tumor prognosis. N-glycosylation of proteins modulates immune responses within the TME. ALG3, a key N-glycosylation enzyme, is involved in protein glycosylation. Although ALG3 expression has been studied in various tumors, its role in regulating the immune microenvironment and its prognostic significance in HCC remain unclear.MethodsThis study comprehensively evaluates ALG3 expression in HCC and its relationship with the immune microenvironment using various techniques. First, bioinformatics analysis of HCC-related data from the TCGA database was performed to investigate ALG3 expression patterns in tumor tissues and its correlation with clinical features. Multiplex immunohistochemistry (mIHC) was then used to validate ALG3 expression in HCC tissue samples and examine its relationship with immune cell infiltration. Additionally, cell experiments and 3D human organoid-based culture models were employed to further assess the role of ALG3 in the HCC immune microenvironment.ResultsThe results showed significant overexpression of ALG3 in HCC tissues, with high expression correlating significantly with poor tumor prognosis. Further analysis revealed that high ALG3 expression was associated with reduced infiltration of CD8+ T cells and CD68+ macrophages in both tumor and stromal areas, while positively correlating with increased infiltration of FOXP3+ regulatory T cells (Tregs). Notably, ALG3 expression levels were also positively correlated with PD-L1 expression in HCC tissues.ConclusionsALG3 may serve as a potential prognostic biomarker and an immunotherapy target in HCC.